2011
DOI: 10.4236/ojmh.2011.12002
|View full text |Cite
|
Sign up to set email alerts
|

Introducing the Mixed Distribution in Fitting Rainfall Data

Abstract: Several types of mixed distribution are proposed and tested in order to determine the best model in describing daily rainfall amount in Peninsular Malaysia for the time period of 33 years. A mixed distribution is a mixture of discrete and continuous daily rainfall which included the dry days. The mixed distributions tested in this study were exponential distribution, gamma distribution, weibull distribution and lognormal distribution. The model will be selected based on the Akaike Information Criterion (AIC). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…The development of the model for the amount process was based on the recommendations by Fernandes et al [9] and Suhaila et al [18]. Specifically, a number of distributions were selected for the purpose of identifying and evaluating the ideal distribution for this process.…”
Section: Amount Processmentioning
confidence: 99%
“…The development of the model for the amount process was based on the recommendations by Fernandes et al [9] and Suhaila et al [18]. Specifically, a number of distributions were selected for the purpose of identifying and evaluating the ideal distribution for this process.…”
Section: Amount Processmentioning
confidence: 99%
“…For instance, Generalized Pareto has been found to be the best distribution of rainfall intensity in Peninsular Malaysia (Dan'azumi et al, 2010) to model the rainfall intensity. Another study found that Mixed Lognormal distribution was the best distribution model for most of the rain gauge stations in Peninsular Malaysia (Suhaila et al, 2011). However, studies by Abas et al (2014) and Daud et al (2016) using Neyman Scott methodology showed that Mixed Exponential was the best distribution to describe the intensity of rainfall in Peninsular Malaysia.…”
Section: Introductionmentioning
confidence: 97%
“…Characterizing variability by fitting a function to some empirical form of the distribution of daily rainfall is another established technique. Whether the function is fit to the empirical frequency distribution [e.g., May, 2004a;Suhaila et al, 2011], the normalized rainfall curve [e.g., Burgueño et al, 2010], or the concentration index [e.g., Martin-Vide, 2004;Jiang et al, 2016;Caloiero, 2014] the result is the same: the actual form of the distribution of daily rainfall variability is summarized by a function with just a few parameters. In order to keep in line with previous work on the importance of climatic variability on long-term landscape evolution [Tucker and Bras, 2000;Tucker, 2004;Lague, 2005;Rossi et al, 2016], we fit a mixture of gamma distributions to the empirical frequency distribution of daily rainfall.…”
Section: Introductionmentioning
confidence: 99%